Utilization of Grits and Dreg Wastes for Ceramics Raw Material - Edwin Kristanto Sijabat; Andrie Harmaji; Rafida Khoirani (Universitas Muhammadiyah Yogyakarta, 2022)
This research utilizes dreg and grits wastes from pulp industry by addition of kaolin as raw material in producing ceramics that have good physical and mechanical properties. Dreg and grits were prepared by drying in an oven at 120°C for 5 hours, then crushed and sieved using a 200 mesh sieve, then characterized by means of Inductively Coupled Plasma (ICP). Ceramic samples were printed using Compressive Gauge Testing with a strength of 15 kN for 60 seconds. The kaolin percentage was varied between 20-80% followed by drying for 48 hours at room temperature. The ceramic samples were burned in a stepwise furnace temperature of up to 1000°C with a holding time of 30 minutes. Their physical properties, i.e. density, porosity, fuel loss, and water absorption, were characterized, and their compressive strength was investigated. The ICP test showed that the highest chemical content in the dreg and grit is CaO, at 36% and 50%. The optimum dose of ceramics produced in this study is the composition of 80% kaolin. The percentage of kaolin mixture is directly proportional to the compressive strength, density and fuel shrinkage, while the porosity and water absorption are inversely proportional. The ceramic characterization was obtained with compressive strength ranging from 4.48 MPa to 11.98 MPa.